CSF Biofire-assisted Rapid Diagnosis of a Case of Cryptococcal Meningoen-cephalitis: A Case Report - Arora, Ekal; Dhamija , Sakshi; Garg , Prachi; Arora , Sonalika; Prakash , Jai; Dangi , Anoop; Arya , Gaurav (Universitas Brawijaya, 2024)
Cryptococcosis causes invasive fungal infections and the two common species are cryptococcus neoformans and cryptococcus gattii, which are responsible for the majority of the clinical manifestations. We are presenting a case of a 35-year-old individual who was admitted with the complaints of fever associated with acute onset altered sensorium. His CSF PCR testing showed cryptococcus species, and so diagnosed as cryptococcal meningoencephalitis and then eventually found to have HIV/AIDS. CSF PCR testing can be done rapidly for variety of common bacterial and fungal infections, and its results are available within one hour. The early diagnosis and treatment initiation is very vital in immunodeficiency states such as HIV, as it can have positive prognostic effect on natural course of disease process. The patient did receive dual anti-fungal drugs, along with Antiretroviral therapy (ARV) and showed drastic clinical improvement.